Korelasi Kurikulum terhadap Hasil Belajar Siswa SMK di Indonesia: Studi Meta Analisis - Prasetyo, Aditya; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze the correlation between curriculum implementation and learning outcomes of Vocational High School (SMK) students in Indonesia through a meta-analysis approach. Meta-analysis was conducted on 50 relevant studies obtained from various National Journals using keywords, such as